Medium access control in real-time vehicular communications - Ferreira, Nuno Fábio Gomes Camacho (2020)
Despite several preventive measures, the number of roadway accidents is still very high, being considered even a problem of public health by some entities. This thesis has as global purpose of contributing to the reduction of that number of accidents, and consequent fatalities, by using safety-related applications that use communication among vehicles. In particular, the primary goal is guaranteeing that communication between users in vehicular environments is done with appropriate time bounds to transfer safety-critical information. In detail, it is studied how to manage the scheduling of message’s transmissions (medium access control - MAC), in order to define precisely who will communicate and when is the appropriate instant. The preferable situation where a communication infrastructure is present with full coverage (RSUs) is also studied, from which medium access control is defined precisely, and vehicles (OBUs) become aware of medium utilization. Also, sporadic situations (e.g., absence of RSUs) are studied in which the communication network is “ad hoc” and solely formed by the current vehicles. It is used the recently WAVE / IEEE 802.11p standard, specific for vehicular communications, and it is proposed a TDMA based solution, with appropriate coordination between RSUs in order to effectively disseminate a critical safety event. It is taken into account two different ways of choosing the instant for the initial broadcast, and both cases are compared. In case there is no infrastructure available, methods are derived to minimize communication medium access collisions, and to maximize the available bandwidth. The results reflect the total end-to-end delay, and show that adequate times are attained, and meet with the requisites for the type of applications being considered. Also, enhancements are obtained when using the alternate choice for the initial broadcast instant.